Paulus im Medienwandel: 2 Kor 3 als Medialitätsnarrativ - Guttenberger, Gudrun (Biblische Zeitschrift, 2019)
In 2 Cor 3 Paul talks about him and Moses as a medium of God. Paul’s argument is analyzed and interpreted with a pivotal concept of mediality: presence. Moses and the Tora are drafted by Paul as opaque, therefore an ineffective media for God’s acting. He, as an apostle, claims to be a transparent medium by which the believers are transformed to media themselves. He proves his claim by the reading process of 2 Cor 3: the performative quality of his text, mainly achieved by effects of immersion, discloses the Spirit’s acting. So Paul’s letter gives life, although the letter kills.